PENGARUH INVESTASI PMA / PMDN DAN JUMLAH PENDUDUK TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DAN PENDAPATAN ASLI DAERAH KOTA SAMARINDA - Doni Julfiansyah (Jurnal Ekonomi Pembangunan, 2013)
The objective of this study is to investigate and analyze whether or not the influence of foreign investment, domestic investment, and the population of the Gross Regional Domestic Product of Samarinda. In addition, to determine and analyze whether or not the influence of foreign investment, domestic investment, and the population of the city of Samarinda Revenue. Analysis of the data used is multiple linear regression analysis. The results showed that: the first model (1) there is a significant relationship between the variables of foreign investment, domestic investment, and the population of the Gross Regional Domestic Product simultaneously. (2) partially only population that significantly affect the Gross Regional Domestic Product. Whereas the second model results indicate that (1) there is a significant relationship between the variables of foreign investment, domestic investment, and the population of the region income simultaneously. (2) partially no good variable Foreign Investment, Domestic Investment, and the number of people who influence the Revenue.